2020
DOI: 10.22463/0122820x.2403
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the relationship between the water retention curve, particle size and pore size distribution in the characterization of a collapsible porous clay

Abstract: In highly porous soils with a susceptibility to collapse, there are points of volumetric variability, due to the present heterogeneity, regarding the diameters of the poral throat. The predominance of a pore size is closely related to certain values of the Water Retention Curve (WRC). However, to date, a possible correlation with particle size distribution (PaSD), obtained using modern, highly reliable gravitational sedimentation methods, has not been studied. The porous clay of lateritic origin under study, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Grain size and mineral composition affect the development of fissility. In general, the silt content is directly related to the random arrangement of clay minerals (Ho et al, 1999;Olarte and Ruge, 2020). Day-Stirrat et al (2010) showed that illite-smectite bedding-parallel orientation is inversely proportional to the whole-rock quartz content.…”
Section: Primary Fissilitymentioning
confidence: 99%
“…Grain size and mineral composition affect the development of fissility. In general, the silt content is directly related to the random arrangement of clay minerals (Ho et al, 1999;Olarte and Ruge, 2020). Day-Stirrat et al (2010) showed that illite-smectite bedding-parallel orientation is inversely proportional to the whole-rock quartz content.…”
Section: Primary Fissilitymentioning
confidence: 99%